American public opinion on the Iraq War - Holsti, Ole R. (University of Michigan Press, 2011)
"A substantial contribution to understanding the role of public opinion and the news media during the Iraq War. Equally impressive, it effectively puts the domestic context of U.S. policy in historical perspective, making the book useful to historians as well as to political scientists."--Ralph B. Levering, Davidson College "American Public Opinion on the Iraq War sets out to chart against a detailed account of the war a nuanced assessment of how public opinion on the conflict evolved, the partisan differences that emerged, how the issue affected other areas of foreign policy opinion, and the limits of public opinion on policy. It succeeds at all of this, and it does so in a manner that is at once informative, inherently interesting, and exceptionally easy to read."--Randolph M. Siverson, University of California, Davis Ole R. Holsti explores the extent to which changes in public opinion reflected the vigorous public relations efforts of the Bush administration to gain support for the war and the partisanship marking debates over policies toward Iraq. Holsti investigates the ways in which the Iraq experience has led substantial numbers of Americans to reconsider their nation's proper international role, and he assesses the impact that public opinion has had on policymakers. Significantly, Holsti places his findings in a broader context to address the role of public opinion and of the media in democratic governance.